2005
DOI: 10.1111/j.1365-3059.2005.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining variation in the effects of take‐all (Gaeumannomyces graminis var. tritici) on nitrogen and water uptake by winter wheat

Abstract: Two field experiments, in 1999 and 2000, were used to test whether reductions in root growth and function explained the effects of take-all on crop water and nitrogen uptake. The fungicide silthiofam was used to manipulate take-all independently of other factors. Soil water content was manipulated from heading to determine effects on disease progress and resource capture. Epidemic progress was significantly delayed in the presence of silthiofam, leading to reductions in disease in both experiments. Effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
2
9
0
1
Order By: Relevance
“…Previous research has shown that the progression of take‐all epidemics from build‐up to TAD is significantly influenced by environmental conditions (Slope & Gutteridge, 1979; Bailey et al. , 2005; Pillinger et al. , 2005; Ennaifar et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that the progression of take‐all epidemics from build‐up to TAD is significantly influenced by environmental conditions (Slope & Gutteridge, 1979; Bailey et al. , 2005; Pillinger et al. , 2005; Ennaifar et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 2007). High soil moisture levels have been associated with more severe take‐all epidemics (Pillinger et al. , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that high soil moisture levels are related to higher severity of take-all (Cook, 2003;Pillinger et al, 2005;Smiley, 2009). Cook (1981) indicated that for take-all to spread it needs a field with high water potential largely for the pathogens to grow and infect the plants in the 25 cm layer of the soil.…”
Section: Discussionmentioning
confidence: 99%
“…tritici (Ggt) DNA concentrations >80 pg. Bateman & Hornby 1999;Bateman et al 2004;Pillinger et al 2005).…”
Section: Discussionmentioning
confidence: 99%